The response to the training load in the aquatic environment in terms of the stimulation of the reflective capabilities of elite synchronized swimmers - Labudová, J.; Rýzková, E.; Raichwalderová, K.; Végh, D.; Slaninová, M.; Vavák, M. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2020)
The youngest swimming sport included in the Summer Olympic Games since 1984 is synchronized swimming. Since the synchronized swimming is still growing popularity and professionalization, it is important to search for ways to improve sports performance. There are few scientific studies focusing also on the biological and motor indicators of top athletes. The present study examined biological and motor variables of elite synchronized swimmers (SYN, N = 13) in ages of 16.5 ± 3.23 years and compare the frequency of Angiotensin Converting Enzyme (ACE) gene genotypes among elite female synchronized swimmers and the non-athletic control group (CON, N = 30) in ages of 16.0 ± 0.6 years. The motor variables were measured using Optojump system before and after water training session. All measurements were collected by trained data collection staff. The ACE I/D variation differences between groups were identified by Chi-Square test. The results of motor variables obtained were evaluated statistically using the Wilcoxon Signed-Rank Test. The strength of association between selected biological and motor variables was measured by Spearman`s correlation. We provided evidence for significant differences of variation of the ACE I/D polymorphism between observed groups. A significant correlation among biological and motor parameters of SYN was demonstrated among the percentage of fat and the time of reflection (p = 0.042), the basal resting heart rate and the jump height (p = 0.006) and among the basal resting heart rate and the power (p = 0.012). The SYN significantly increased only their contact time in jumping (p < 0.016) after the training session. Based on the results we state that the effect of intervention in the stimulation of the reflective capabilities due to the training session in the aquatic environment was not confirmed in the study.